Leveraging Instagram for the Development of Sustainable Tourism MSMEs in Pampang Cultural Village, East Kalimantan - Sinta Paramita; Farid Rusdi; Joana Jaya; Agustina Kahumako (Jogjakarta Communication Conference (JCC), 2026)
The use of Instagram to develop micro, small, and medium enterprises (MSMEs) in the sustainable tourism sector of Pampang Cultural Village represents a strategic approach to promoting the area's cultural and natural assets.  As a visual-based social media platform, Instagram facilitates the effective dissemination of information through engaging, accessible photo, video, and story content. Authentic, creative, and consistent content helps increase public awareness of the distinctive local culture, traditions, and tourist attractions. This initiative forms part of the Community Service (PKM) program, which seeks to enhance MSME capacity in effective social media management. The implementation methods include analyzing the Pampang Cultural Village Instagram account, facilitating discussions and mentoring account managers, and conducting continuous monitoring and evaluation.  This approach supports sustained management of effective, targeted content. The outcomes of this activity indicate improved skills in content creation, the formulation of structured promotional strategies, and the use of storytelling to emphasize cultural values in product marketing, including souvenirs. These advancements have enhanced the village's visibility, increased both local and international tourist visits, and strengthened the community's economy while maintaining a commitment to cultural and environmental preservation.